Immediate postoperative imaging after uncomplicated endoscopic approach to the anterior skull base: is it necessary?. Issue 12 (4th September 2014) - Nadimi, Sahar; Caballero, Nadieska; Carpenter, Patrick; Sowa, Lauren; Cunningham, Ryan; Welch, Kevin C.
<x xml:space="preserve">Abstract</x> Background Postoperative imaging is frequently performed to assess for intracranial complications following anterior skull base (ASB) surgery. However, there is little data to suggest that radiologic studies change the management of complications. In this study, the utility of postoperative imaging within 72 hours after uncomplicated ASB surgery was examined. Methods A retrospective review was conducted of 143 patients who underwent endoscopic ASB surgery between 2007 and 2013 at Loyola University Medical Center. The main outcomes measures included the ability of head computed tomography (CT) scan to identify postoperative complications and hallmark symptoms associated with complications. Results Seventy‐nine patients underwent postoperative imaging within 72 hours of the initial surgery. The most common finding was pneumocephalus (35/79; 44%). Expanding pneumocephalus requiring surgical intervention developed in 3 cases. Cerebrospinal fluid (CSF) leak was the most common complication, occurring in 22 of 143 (15%) of the patients. Of the 24 patients who developed a postoperative complication, all had clinical signs or symptoms indicative of the need for surgical or medical intervention. The positive predictive value for a head CT scan to detect a complication was 12%, negative predictive value was 92%, and sensitivity and specificity were 63% and 48%, respectively. Conclusion Routine postoperative imaging may be unnecessary after uncomplicated endoscopic ASB surgery because (1) it may not alter patient management; (2) it may not detect the most common complication (CSF leak); and (3) when imaging is positive, the patient has clinical symptoms suggesting a need for intervention.